Hubungan Derajat Aktivitas Fisik pada Laki-Laki dengan Kejadian Stroke Iskemik di RSUD Dr Moewardi Surakarta - Hermawan, Yusuf Budi; Soedomo, Agus; Wijayanti, Lilik (Nexus Kedokteran Klinik, 2013)
BackgroundÂ Â Â  : Stroke is a disease caused high morbidity and mortality rate in low-middle income countries. Low physical activity is one of the risk factors for ischemic stroke. The impact of low physical activity is high level of NADPH, atherosclerosis, and vascular elasticity disorder. Global Physical Activity Questionnaire version 2 (GPAQv2) is a questionnaire released by WHO which has been especially designed to measure the physical activity of people in developing countries. The aim of this study is to determine the correlation between man physical activities and ischemic stroke in Dr Moewardi Hospital Surakarta. Methods: This was an analytical observational study with case control approach. This study was conducted during May - July 2013 at the Neurology Department of Dr. Moewardi Hospital Surakarta. Subjects were acute ischemic stroke patients in neurology ward of Dr. Moewardi Hospital Surakarta which were taken by using fixed disease sampling. Data were collected by interviewed patients based on GPAQv2 questionnaire. Data analysis used multivariate with double logistic regression and have been processed by Statistical Product and Service Solution (SPSS) 16.00 for Windows. Results: This study showed statistically significant (p=0,036) between man physical activities and acute ischemic stroke in Neurology Department Dr. Moewardi Hospital Surakarta. Age and smoking as comfounding factors have been controlled. Male patients with low physical activity had 13.95 times (OR = 13.95; CI 95% 1.19 â 163.58) to develop ischemic stroke than ones with adequate physical activity. Conclusion:Men who use to have less physical activity more likely to develop ischemic stroke. Keywords : level of physical activity, acute ischemic stroke, GPAQv2Â